Effect of Planting Dates on the Yield and Quality of True Seeds of Onion - Mollah, M. R. A.; Ali, M. A.; Ahmad, M.; Hassan, M. K.; Alam, M. J. (International Journal of Applied Sciences and Biotechnology, 2015)
The present study was stimulated by the problem of onion seed production where seed production is possibly only winter period after whichrapid increase in temperature as well as early shower adversely affect the quality of seed. To overcome this situation a field experiment wasundertaken to find out the optimum planting time for maximizing quality true seeds of onion. The experiment was laid out in a randomizedcomplete block design with four replications. The treatments were five planting dates viz. 1 October, 15 October, 30 October, 15 Novemberand 30 November to achieve the objective. The research work was done at On-Farm Research Division, BARI, Bogra during September, 2010to June, 2011. The results revealed that the growth parameters, seed yield components, health and quality of harvested seeds were significantlyinfluenced by the different treatments. Results showed that among different planting dates, 15th November was the best for seed and quality.DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.11847     Int J Appl Sci Biotechnol, Vol. 3(1): 67-72